If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6 = 7x + 12 Reorder the terms: -6 + 4x = 7x + 12 Reorder the terms: -6 + 4x = 12 + 7x Solving -6 + 4x = 12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6 + 4x + -7x = 12 + 7x + -7x Combine like terms: 4x + -7x = -3x -6 + -3x = 12 + 7x + -7x Combine like terms: 7x + -7x = 0 -6 + -3x = 12 + 0 -6 + -3x = 12 Add '6' to each side of the equation. -6 + 6 + -3x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 12 + 6 -3x = 12 + 6 Combine like terms: 12 + 6 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| f(x+6)=x^2-6x+4 | | 8d+4d+6d-6-2d=0 | | x+2(x+5)=35 | | 8x+8=8x-1 | | 3a-(12-a)=16 | | 5x+3-2x=-2 | | 3-3(4-8x)=0 | | 0.72-1.4= | | h=-16tsquared+48t+4 | | 1x=4y-7 | | .3x-.5=.2x+8 | | 12x-4+18x+4+15x+10+5=360 | | 6x-6-3x-3=-6 | | -4x+4x=-8-32 | | w+5-(2w+5)=5 | | y=1/0 | | I/3+6=10 | | 8=4u+53+5u | | y=1/1-1 | | 3g+57g+4= | | 0.6x-.3=.5x+5 | | 3-6(8x+2)=9 | | 4x+(-8)=12 | | 5x+4y=79 | | 3-(r+3)=-14-3r | | -2x+6x=45 | | 5x+4x=79 | | -2(3t-5)+4t=5t-6 | | 8-4x+7=5x+30-2 | | 5(x+1)+8=3x+2(5+x) | | 18x-48y= | | 3(x+5)=4 |